2015
DOI: 10.1007/s00726-015-2041-y
|View full text |Cite
|
Sign up to set email alerts
|

d-Amino acids incorporation in the frog skin-derived peptide esculentin-1a(1-21)NH2 is beneficial for its multiple functions

Abstract: Naturally occurring antimicrobial peptides (AMPs) represent promising future antibiotics. We have previously isolated esculentin-1a(1-21)NH2, a short peptide derived from the frog skin AMP esculentin-1a, with a potent anti-Pseudomonal activity. Here, we investigated additional functions of the peptide and properties responsible for these activities. For that purpose, we synthesized the peptide, as well as its structurally altered analog containing two D-amino acids. The peptides were then biophysically and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 92 publications
(90 reference statements)
12
70
0
Order By: Relevance
“…As reported for A549 cells (36), the diastereomer is more effective in inducing reepithelialization of the wounded area, with a mechanism that implies an EGFRmediated signaling pathway. We think that the lower woundhealing efficacy of the more helical Esc(1-21) compared to its diastereomer is a consequence of a stronger alteration of the phospholipid membrane region where EGF receptors are located.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…As reported for A549 cells (36), the diastereomer is more effective in inducing reepithelialization of the wounded area, with a mechanism that implies an EGFRmediated signaling pathway. We think that the lower woundhealing efficacy of the more helical Esc(1-21) compared to its diastereomer is a consequence of a stronger alteration of the phospholipid membrane region where EGF receptors are located.…”
Section: Discussionsupporting
confidence: 67%
“…In a previous study (36), it was reported that both Esc(1-21) and its diastereomer, Esc(1-21)-1c, are not toxic to A549 epithelial cells up to 64 M, and that the diastereomer is substantially less toxic when used at higher concentrations (36). Although A549 cells possess morphological and biochemical properties of alveolar epithelial cells (type II pneumocytes) (17), they do not express CFTR (43,44).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations